Epistemology and diffusion of knowledge: Bases for the construction of knowledge in the application research in the education of young people and adults of SESI Bahia - Freitas, Gisele Marcia de Oliveira; Silva , Francisca de Paula Santos da; Matta , Alfredo Eurico Rodrigues; Amorim , Antonio; Santos , Reinaldo de Jesus; Silva , Fernanda Brito da; Miyamoto , Hitomi Pires; Jesus , Rafaela Mota Giffone de; Mazzei , Leliany Roberica Rocha Bomfim; Luz , Diana Maria Bezerra Gonçalves (Seven Editora, 2023)
This work presents the epistemological bases, the first definitions, as well as possible referrals, surveys and analyses that will sustain the applied research that has been carried out within the scope of the Doctorate in Diffusion of Knowledge. The problem of the doctoral scientific work is: what is the contribution of teacher training in digital information and communication technologies to the pedagogical practice in the Education of Youth and Adults at a Distance of SESI Bahia? The locus of scientific research is the SESI School Rector Miguel Calmon, located in Retiro, in the city of Salvador – Bahia, located in the region of the Old Quilombo do Cabula. The epistemological conception adopted in this scientific research is socioconstructivist. The research approach used for the construction of this article was qualitative research instrumentalized by a bibliographic research. The results point to an epistemological research based on socioconstructivism and supported by the methodology of Application Research, which is an innovative research approach for bringing together the advantages of qualitative and quantitative methodologies. DOI:https://doi.org/10.56238/devopinterscie-276